2008
DOI: 10.1021/np800017x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase (COX)-1 and -2 Inhibitory Labdane Diterpenes from Crassocephalum mannii

Abstract: Two new labdane diterpenes, 8alpha,19-dihydroxylabd-13 E-en-15-oic acid (1) and 13,14,15,16-tetranorlabdane-8alpha,12,14-triol (2), as well as an acetylated derivative, 8alpha-O-beta-D-glucopyranosyllabd-13 E-ene-15,19-diol-8alpha-2',3',4',6'-hexaacetate (3a), were isolated from the aerial parts of Crassocephalum mannii. The structures of 1, 2, and 3a were elucidated by spectroscopic data analysis. Selective inhibitory activity for 1 and 2 and their acetate derivatives, 1a and 2a, against cyclooxygenases (COX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Two compds. Anti-cyclooxygenases (Hegazy, et al, 2008) Cryptococcus neoformans (Kita, et al, 2007a) Elsholtzia rugulosa Protein toxin TOF Genetics of biosynthesis (Nolan, et al, 2007) Lethasterias fusca (Far Easterm starfish)…”
Section: Labdane Diterpene Glycosides Tof Nmr Hplcmentioning
confidence: 99%
“…Two compds. Anti-cyclooxygenases (Hegazy, et al, 2008) Cryptococcus neoformans (Kita, et al, 2007a) Elsholtzia rugulosa Protein toxin TOF Genetics of biosynthesis (Nolan, et al, 2007) Lethasterias fusca (Far Easterm starfish)…”
Section: Labdane Diterpene Glycosides Tof Nmr Hplcmentioning
confidence: 99%
“…Therefore, after isolation, it is crucial to understand the pharmacological properties of these plant-based compounds. Previous studies have identified several plant-derived compounds, including labdane [9, diterpenes, capable to inhibit COX-1 and/or COX-2 13] . In the present work, three diterpenoids isolated from P. ornatus were evaluated for a potential COX-1 inhibitory effect, using a functional assay, based in the peroxidase component of COX.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, após isolamento, é fundamental compreender as propriedades farmacológicas de compostos derivados de plantas. Estudos anteriores identificaram diversos compostos derivados de plantas, incluindo diterpenos com esqueleto de labdano, com capacidade de inibir a [9,13] COX-1 e/ou a COX-2…”
Section: Discussionunclassified
“…Phytochemical screening indicated A. membranaceum to contain mainly triterpenoids and alkaloids while C. manii contains mainly triterpenoids. The literature indicated that these classes of compounds are widely reported from these genera displaying different biological activities (Bringmann et al, 2000;Chhabra et al, 1984;Hegazy et al, 2008;Steenkamp et al, 2009). Comparing the activities of extracts six medicinal plants under this investigation and the standard antibiotics, Ciprofloxacin had much higher activities than all plant extracts.…”
Section: Phytochemical Screeningmentioning
confidence: 99%